Me-search? Search me! A new twist in the tale of introspection. Issue 13 (2nd September 2021) - Brown, Stephen; Patterson, Anthony
ABSTRACT: According to James Lovelock of Gaia hypothesis fame, it takes thirty years for innovative ideas to gain acceptance and forty before the heterodox becomes orthodox, all proper and correct and enshrined in textbooks. Thirty years after Stephen Gould's heretical article on Introspection and the best part of forty years since Morris Holbrook took up his pen, the time is right to evaluate their ideas. Less a rigorous investigation than an irreverent reflection on a reflective research method, this paper summarises the state of the art of introspection – and some of its many permutations – in an appropriately artistic manner.